Delayed Pancreatic Fistula After Pancreaticoduodenectomy. A Case Report - Ito, Yasuhiro; Irino, Tomoyuki; Egawa, Tomohisa; Hayashi, Shinobu; Nagashima, Atsushi (JOP. Journal of the Pancreas, 2011)
Context Pancreatic fistulas still occur despite refinements in both surgical technique and perioperative management after a pancreaticoduodenectomy. However, the occurrence of delayed pancreatic fistulas is very rare. Case report A 62-year-old woman diagnosed with a lower biliary carcinoma had undergone a pylorus-preserving pancreaticoduodenectomy. The postoperative course was uneventful and the patient was discharged from the hospital after 16 days. One year after surgery, she was admitted to our hospital with a fluid collection around the pancreaticojejunal anastomosis. A catheter was inserted percutaneously and the fluid collection was drained. The amylase value of the discharge was significantly elevated (119,500 IU/L). One week later, a fistulography showed no significant collection and the tube was clamped. The patient was discharged from the hospital without symptoms. Conclusions It is important to consider the occurrence of a delayed pancreatic fistula if the patient suffers from any symptoms. It is then necessary to proceed rapidly. Image: Fistulography showing the disappearance of the fluid collection around the pancreaticojejunal anastomosis.